Properties and rapid sintering of nanostructured WC and WC-TiAl hard materials by the pulsed current activated heating - Jung, Ga-Na; Kim, Byung-Su; Yoon, Jin-Kook; Shon, In-Jin (세라믹공정연구센터, 2016)
In the case of cemented WC, Ni or Co is added as a binder for the formation of composite structures. However, the high cost of Ni or Co, the low hardness and the low corrosion resistance of the WC-Ni and WC-Co cermets have generated interest in recent years for alternative binder phases. In this study, TiAl was used as a novel binder and consolidated by the pulsed current activated sintering (PCAS) method. Highly dense WC-TiAl with a relative density of up to 99% was obtained within 2 min by PCAS under a pressure of 80MPa. The method was found to enable not only the rapid densification but also the inhibition of grain growth preserving the nano-scale microstructure. The addition of TiAl to WC enhanced the toughness without great decrease of hardness due to crack deflection and decrease of grain size.